KAJIAN PENGGUNAAN ZAT PENGATUR TUMBUH INDOLE BUTYRIC ACID (IBA) TERHADAP PENINGKATAN PERTUMBUHAN STEK BATANG TANAMAN MURBEI (Morus alba L.) - Arini, Nindya (Universitas Muria Kudus, 2024)
Mulberry (Morus alba L.) is an important commodity in the silkworm farming industry and has high economic value, thus requiring efficient propagation techniques. Vegetative propagation through stem cuttings is often constrained by a low success rate of root formation. IBA (Indole Butyric Acid), as a synthetic auxin hormone, plays a significant role in stimulating root development in plants. This study aims to determine the effect of concentration and soaking duration of the plant growth regulator Indole Butyric Acid (IBA) on the growth enhancement of mulberry (Morus alba L.) stem cuttings. The research was conducted at the Seed House of the Experimental Garden, Faculty of Agriculture, Universitas Muria Kudus, located in Gondangmanis Village, Bae Sub-district, Kudus Regency, from May to July 2024. The study employed a Completely Randomized Block Design (CRBD) consisting of two factors with three replications. The first factor was IBA concentration (K), namely K1 (100 ppm), K2 (200 ppm), and K3 (300 ppm). The second factor was soaking duration (L), namely L1 (60 minutes) and L2 (120 minutes). The results showed that different concentrations of Indole Butyric Acid had an effect on root length, time of bud emergence, and shoot length at 3 weeks after planting (WAP), while soaking duration influenced root length. A significant interaction between IBA concentration and soaking duration was observed on root length.